Multi-System Inflammatory Syndrome in Neonates (MIS-N) - Clinical Profile and Outcomes - A Prospective Cohort Study (International Journal of Child Health and Nutrition, 2023)
Aims: To analyze the clinical spectrum in Neonates with MIS-N based on the time of presentation and also to assess the use of immunomodulator therapy in MIS-N.Subjects and Methods: We studied 100 neonates delivered at BLDE (DU) Shri B M Patil Medical College Hospital admitted to Level III-A NICU from JULY 2020 to MAY 2021. 98 neonates had high titers of IG G antibodies and were negative for COVID Antigen. We categorized the cohorts into EARLY MIS-N (72 hrs).Results: 58 presented as EARLY MIS-N with Respiratory distress (RD) in 40 (70%), cardiac dysfunction 34 (60%), PPHN 12(20%), Fever 12(20%), seizures 12(20%), encephalopathy in 6(10%), sepsis-like features 6(10%), had elevated inflammatory markers like CRP (30%), D-Dimer (70%), Ferritin (30%), cardiac biomarkers like BNP (60%), LDH (30%) and ECHO showing LV dysfunction in 50%. LATE MIS-N presented mostly with fever 28(70%), sepsis-like features 24(60%), Respiratory Distress in 16(40%), cardiac dysfunction 12 (30%), hypoglycemia 4(10%), parotitis 4(10%), had significantly elevated inflammatory markers like CRP (70%), D-Dimer (50%), Ferritin (70%), cardiac biomarkers like BNP (40%), LDH (20%) and ECHO showing LV dysfunction in 20%, dilated coronaries in 20 %, PPHN in 10%. Oxygen and respiratory support requirements were higher in EARLY presenters and IVIG and steroid requirements were more in LATE presenters.Conclusion: We observed that maternal SARS-COV-2 antibodies transferred transplacentally and neonatal antibodies acquired after COVID-19 infection can cause MIS-N in neonates. Immunomodulator therapy is required in severe cases of MIS-N only.